The moderating effect of banking sector employees' abilities, motivation, and opportunities (AMO) on the relationship between corporate culture and their entrepreneurial mindset and behaviour - Botha, Melodi (University of Pretoria, 2026)
Mini Dissertation (MBA)--University of Pretoria, 2025.